Health Information Exchange between Specialists and General Practitioners Benefits Rural Patients - Nakayama, Masaharu; Inoue, Ryusuke; Miyata, Satoshi; Shimizu, Hiroaki (Applied Clinical Informatics, 2021)
Background Health information exchange (HIE) may improve diagnostic accuracy, treatment efficacy, and safety by providing treating physicians with expert advice. However, most previous studies on HIE have been observational in nature.Objectives To examine whether collaboration between specialists and general practitioners (GPs) in rural areas via HIE can improve outcomes among patients at low-to-moderate risk of cardiovascular disease, kidney disease, and stroke.Methods In this randomized controlled trial, the Miyagi Medical and Welfare Information Network was used for HIE. We evaluated the clinical data of 1,092 patients aged ≥65 years living in the rural areas of the Miyagi Prefecture and receiving care from GPs only. High-risk patients were immediately referred to specialists, whereas low-to-moderate risk patients were randomly assigned to an intervention group in which GPs were advised by specialists through HIE (n = 518, 38% male, mean age = 76 ± 7 years) or a control group in which GPs received no advice by specialists (n = 521, 39% male, mean age = 75 ± 7 years).Results In the intention-to-treat analysis, all-cause mortality and cumulative incidence of serious adverse events (e.g., hospital admission or unexpected referral to specialists) did not differ between the groups. However, per-protocol analysis controlling for GP adherence with specialist recommendations revealed significantly reduced all-cause mortality (p = 0.04) and cumulative serious adverse event incidence (p = 0.04) in the intervention group compared with the control group.Conclusion HIE systems may improve outcomes among low-to-moderate risk patients by promoting greater collaboration between specialists and GPs, particularly in rural areas with few local specialists.
Keywords: cardiovascular disease; health information exchange; kidney disease; stroke